2017
DOI: 10.7150/thno.21630
|View full text |Cite
|
Sign up to set email alerts
|

Acute Inflammatory Response Following Increased Blood-Brain Barrier Permeability Induced by Focused Ultrasound is Dependent on Microbubble Dose

Abstract: Rationale: Focused ultrasound (FUS), in conjunction with circulating microbubbles (MBs), can be used to transiently increase the permeability of the blood-brain barrier (BBB) in a targeted manner, allowing therapeutic agents to enter the brain from systemic circulation. While promising preclinical work has paved the way for the initiation of 3 human trials, there remains concern regarding neuroinflammation following treatment. The aim of this study was to assess the magnitude of this response following sonicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
241
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(267 citation statements)
references
References 37 publications
16
241
2
Order By: Relevance
“…rhFGF20 was found to protect against BBB disruption through upregulating junction protein expression via the AKT/GSK3β pathway and decreasing the inflammatory response via the JNK/NFκB pathway. In our research, we found that the NFκB inhibitor Bay 11-7082 also protected against TNF-αinduced BBB injury in terms of changes to BBB permeability and endothelial resistance, which is consistent with a previous study showing that the NFκB pathway plays an important role in BBB disruption [63]. Notably, the protective effect of rhFGF20 was better than that of Bay 11-7082.…”
Section: Tbisupporting
confidence: 92%
“…rhFGF20 was found to protect against BBB disruption through upregulating junction protein expression via the AKT/GSK3β pathway and decreasing the inflammatory response via the JNK/NFκB pathway. In our research, we found that the NFκB inhibitor Bay 11-7082 also protected against TNF-αinduced BBB injury in terms of changes to BBB permeability and endothelial resistance, which is consistent with a previous study showing that the NFκB pathway plays an important role in BBB disruption [63]. Notably, the protective effect of rhFGF20 was better than that of Bay 11-7082.…”
Section: Tbisupporting
confidence: 92%
“…In this study, we used the recommended clinical imaging dose of Definity microbubbles (20 l/kg) to approximate an equivalent microbubble dose between animals. Recently, McMahon and Hynynen (34) reported that Definity at 20 l/kg compared to 100 l/kg (10 times higher than the clinical imaging dose) can be used to increase BBB permeability without activation of inflammatory markers (i.e., nuclear factor B signaling pathway genes), tissue damage, or MRI evidence of edema and hemorrhage. The probability of FUS-induced BBB permeability using a clinical imaging dose of Definity and Optison is similar across a range of pressure amplitudes, as the ones achieved in our study and established previously by McDannold et al (37).…”
Section: Discussionmentioning
confidence: 99%
“…3 Though conventional hypothesis suggests the brain is an 'immune privilege' tissue, increasing studies indicate that brain disorders are affected by multiple immune factors, such as TNF-α and NF-κB. [4][5][6] While 'immune privilege' is the main contributor to its poor prognosis, few effective therapeutic strategies exist for glioma due to the blood-brain barrier. 7 Glioblastoma patients have a poor survival of 14-17 months in clinical investigations.…”
Section: Introductionmentioning
confidence: 99%